Improving preoperative breast reconstruction consultations: a qualitative study on the impact of personalised audio-recordings - Josipa Petric (BMC, 2021)
Abstract Background To investigate the value of audio-recordings in aiding patient understanding and recall of preoperative breast reconstruction information. Methods This was a prospective cohort study. Participants were randomly allocated into either a recording group who were offered the opportunity to record their breast reconstruction explanation of surgery, or a standard information package group who received standard care. The value of having an audio-recording was assessed by semi-structured interviews and analysis of recurring themes. Results Between 21/2/19 and 19/3/20, 32 women attending consultations for breast reconstruction consented to participate in the study, 17 were randomly assigned to the recording group and 15 the standard information package group. Twenty-eight of the 32 participants completed qualitative interviews. All participants agreed that audio-recordings were a beneficial resource which allowed them to have a better understanding of the concepts discussed. Commonly reported themes included the ability to listen to the recording multiple times to refresh memory, as well as usefulness in helping to inform other family members. Participants also reported increased levels of trust in their clinician for allowing the audio-recordings. Very few participants raised any medico-legal implications of the recordings, their focus was more on the potential of the audio-recordings to alleviate the overwhelming nature of a pre-operative breast reconstruction consultation. Conclusions There was a positive response from participants to the use of audio-recordings in the setting of breast reconstruction consultations. These types of recordings could potentially be used in other complex appointments where detailed information is discussed, with similar success.